Bilateral 'kissing' molars: A case report. Issue 11 (12th November 2022) - Aslam‐Pervez, Bilal; Carr, Emma
Abstract: 'Kissing molars', were described by Van Hoof in 1973 as when the occlusal surfaces of impacted molars are united by the same follicular space and the roots point in the opposite direction. There are very few published cases in the literature, and it is an extremely rare form of impaction. Abstract : This manuscript concerns the diagnosis and management of a rare dentoalveolar clinical and radiographic presentation, which may be encountered by and be of interest to dental practitioners in both primary and secondary care.